Genome-wide identification and transcriptomic analysis of the MAPK family provides insights into the molecular basis of disease resistance of postharvest eggplant in response to Botrytis cinerea - Zhang, Wenxuan; Ming, Yucheng; Ji, Dongchao (Frontiers in Plant Science, 2025)
Eggplant (Solanum melongena), an important crop for food supply, can suffer from severe gray mold rot caused by Botrytis cinerea, resulting in huge postharvest damage every year. Mitogen-activated protein kinase (MAPK) cascades, important to the signal transduction pathway, were identified in many species and proved to be involved in plant growth, development, and immune response, although our knowledge of this cascade in eggplant is scarce. In this work, based on the state-of-art genome sequencing data, the MAPK cascades of eggplant were identified. The result showed that there were 117 MAP3Ks, 5 MAP2Ks, and 16 MAPKs in the eggplant genome. All the proteins possessed traditional MAPK domains. Phylogenetic and collinear analysis showed that eggplant MAPKs was homologous with Arabidopsis and tomato. Cis-acting element analysis indicated that eggplant MAPKs may participate in defense and stress responsiveness. Meanwhile, transcriptomic analysis of postharvest eggplant after Botrytis cinerea infection showed that most of the MAPK genes had altered expression; further functional assays indicate that SmMAP3K38 likely operates as a negative regulator of eggplant immunity against Botrytis cinerea infection, which provides us new insights into the molecular basis of this important crop in disease resistance to Botrytis cinerea and gives us new potential targets for the prevention and control of gray mold.